Auditory imagery forces motor action. Issue 3 (11th February 2015) - Landry, Simon P.; Pagé, Sara; Shiller, Douglas M.; Lepage, Jean-François; Théoret, Hugo; Champoux, François
Abstract : A large number of neuroimaging studies have investigated imagined sensory processing and motor behaviours. These studies have reported neural activation patterns for imagined processes that resemble those of real sensory and motor events. The widespread use of such methods has raised questions about the extent to which imagined sensorimotor events mimic their overt counterparts, including their ability to elicit sensorimotor interactions. Direct behavioural evidence of imagery-induced multisensory interactions has been found recently in tasks involving auditory and visual processing. An influence of sensory imagery on the control of motor action, however, has not been investigated previously. Here, we show that both real and imagined moving sounds induce involuntary ocular movement in a nonvisual tracking task. The present data build on the results of previous studies of sensory imagery by showing that such conditions activate sensory neural areas. Moreover, we show an engagement of functional sensorimotor networks for imagined stimuli in a manner similar to the processing of real auditory stimuli.